Surf-for-Development: An Exploration of Program Recipient Perspectives in Lobitos, Peru. (December 2019) - Mach, Leon
Critical sport for development and peace (SDP) and sustainable surf tourism (SST) research calls for sports programming and research that adheres not only to the desires and needs of local communities but also for movements away from neoliberal development models. This case study, derived from interviewing participants 4 years after partaking in a learn-to-surf program in Lobitos, Peru, suggests that these two broad goals may be contradictory. Leveraging skills and traits adopted from participating in the surf program were seen as important contributions to both individual (i.e., gender and economic empowerment) and community benefits (i.e., re-imagining Lobitos). These findings shed light on the need to better understand program recipient desires for local "reforms" and how they can best be served by SDP programs.